2020
DOI: 10.1093/gerona/glaa252
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity in Early- and Mid-Adulthood Are Independently Associated With Longitudinal Memory Trajectories in Later Life

Abstract: Background Physical activity (PA) in later-life may reduce dementia risk, but little is known regarding long-term cognitive effects of PA that occurred earlier in adulthood or mechanisms underlying associations. PA patterns at different ages may independently contribute to dementia risk, which would implicate multiple critical periods for intervention. The current study tested whether retrospective reports of PA in early- and mid-adulthood were independently associated with later-life longitu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 57 publications
0
9
0
Order By: Relevance
“…We found that participants reported high levels of engagement in healthy lifestyle behaviors related to exercise (mean 3.4 d/wk), diet (60% reported a healthy/balanced diet), and cognitive stimulation (52% engaging in cognitive stimulation 3 to 7 d/wk), all of which may mitigate future cognitive decline. 22 These findings contrast with evidence from large community adult samples showing that few people engage in healthy lifestyle behaviors, 23 particularly related to physical activity among older adults. 24 It is likely that our group was motivated toward dementia prevention given that they volunteered for the registry and that many had risk factors for dementia, including family history of dementia (79%) and SMD (46%).…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…We found that participants reported high levels of engagement in healthy lifestyle behaviors related to exercise (mean 3.4 d/wk), diet (60% reported a healthy/balanced diet), and cognitive stimulation (52% engaging in cognitive stimulation 3 to 7 d/wk), all of which may mitigate future cognitive decline. 22 These findings contrast with evidence from large community adult samples showing that few people engage in healthy lifestyle behaviors, 23 particularly related to physical activity among older adults. 24 It is likely that our group was motivated toward dementia prevention given that they volunteered for the registry and that many had risk factors for dementia, including family history of dementia (79%) and SMD (46%).…”
Section: Discussionmentioning
confidence: 77%
“…This study characterized levels of engagement in healthy lifestyle behaviors, knowledge about modifiable risk factors for dementia, and potential facilitators and barriers to engagement in these behaviors in an AD prevention registry. We found that participants reported high levels of engagement in healthy lifestyle behaviors related to exercise (mean 3.4 d/wk), diet (60% reported a healthy/balanced diet), and cognitive stimulation (52% engaging in cognitive stimulation 3 to 7 d/wk), all of which may mitigate future cognitive decline 22. These findings contrast with evidence from large community adult samples showing that few people engage in healthy lifestyle behaviors,23 particularly related to physical activity among older adults 24.…”
Section: Discussionmentioning
confidence: 94%
“…Outside of work, Iso-Markku et al (2016) found that participants who consistently engaged in vigorous physical activity during midlife had a lower chance of impaired cognition compared to persistently inactive participants. Similarly, Kraal et al (2021) found that level of physical activity during midlife not only predicted higher levels of memory in later life but more exercise was also associated with slower cognitive decline. In addition, more social engagement during middle age has been found to be associated with less cognitive decline later in life (Marioni et al, 2012(Marioni et al, , 2014.…”
Section: Midlife Enrichmentmentioning
confidence: 89%
“…Responses could have been affected by social desirability bias and the degree of over-reporting may be influenced by individual perceived and measured weight status (Ferrari et al, 2007; Warner et al, 2012). Our PA measure is an estimate of METs based on the frequency of engaging in light, moderate, and vigorous activities (Latham & Williams, 2015; Li et al, 2019; Kraal et al, 2021; Nicklett et al, 2020). Although no studies have yet validated this measure, prior studies have assessed the validity and reliability of estimating METs based on an established self-reported PA questionnaire (Craig et al, 2003; Sember et al, 2020).…”
Section: Discussionmentioning
confidence: 99%